Molecular gastronomy - Tymofeev, Konstantin (My University, 2014)
Molecular gastronomy is a subdiscipline of food science that seeks to investigate the physical and chemical transformations of ingredients that occur while cooking. Its programme includes three axis, as cooking was recognized to have three components, which are social, artistic and technical. Molecular Cooking is one application of molecular gastronomy; it means cooking with modern tools. Molecular Cuisine is a modern style of cooking, and takes advantage of many technical innovations from the scientific disciplines.
Keywords: cooking; style; кулінарія; стиль; гастрономія; gastronomy; кафедра іноземних мов професійного спрямування